Literasi Digital Bagi Remaja di DKI Jakarta pada Fenomena Display of Violence di Media Sosial - Putri, Citra Eka; Hamzah, Radja Erland (Jurnal Pustaka Komunikasi, 2024)
This research aims to provide an understanding of digital literacy to the wider community, especially to teenagers who use social media in DKI Jakarta so that they become agents of change from the dangers of the display of violence phenomenon (indulging in acts of violence on social media) to become positive intervention Bystanders who can exercise control. social media by observing the situation and being able to act firmly to help and stop all forms of violence on social media. The research method used is a case study, a type of qualitative descriptive research. Data collection techniques were done through observation, interviews, and document study. The results of the research show that the implementation of digital display of violence literacy among high school students in Jakarta is by looking at data which shows that teenage netizens in Indonesia still do not make positive comments or dare to speak up on social media regarding many things, including the issue of violence as part of bystander intervention. positive, there is a need for collaboration between the government and teaching staff, especially lecturers, to actively carry out digital literacy among teenagers.